2013
DOI: 10.1590/s0100-06832013000400020
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient extraction and exportation by common bean cultivars under different fertilization levels: I - macronutrients

Abstract: SUMMARYThe use of cultivars with a higher yield potential and the adoption of new technology have achieved high grain yields in common bean, which probably changed the demand for nutrients in this crop. However, there is almost no information about the periods of the cycle in which nutrients are most demanded at which quantities by the main cultivars. The objective of this study was to evaluate the macronutrient extraction and exportation by the common bean cultivars Pérola and IAC Alvorada, under different le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
5

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 12 publications
4
32
0
5
Order By: Relevance
“…Since water is the main interference factor in plant physiological processes (Gouveia Neto, 2011), and its restriction triggers plant phenological development acceleration, DM and nutrient partitioning between the different plant organs is changed. Although developing grains act as strong photoassimilate sinks in the plant (Dantas Júnior et al, 2010;Soratto et al, 2013;Santos et al, 2015), in the season cultivation, where there was greater water availability (Figure 1), DM allocation to stem and leaf growth was high, even after flowering (Figure 2e, f, g, h), confirming reports that stress affects photoassimilate partitioning in plants (Thornley, 1972;Cruz et al, 2004).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Since water is the main interference factor in plant physiological processes (Gouveia Neto, 2011), and its restriction triggers plant phenological development acceleration, DM and nutrient partitioning between the different plant organs is changed. Although developing grains act as strong photoassimilate sinks in the plant (Dantas Júnior et al, 2010;Soratto et al, 2013;Santos et al, 2015), in the season cultivation, where there was greater water availability (Figure 1), DM allocation to stem and leaf growth was high, even after flowering (Figure 2e, f, g, h), confirming reports that stress affects photoassimilate partitioning in plants (Thornley, 1972;Cruz et al, 2004).…”
Section: Resultssupporting
confidence: 82%
“…Nutrients with high plant mobility, such as N and P, underwent remobilization from other plant parts, especially from leaves to growing grains (Crusciol et al, 2012a;Soratto et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the N applied pre-sowing improved the NUE with a pronounced effect on the biomass yield (Table 4). Although the maximum uptake of this element occurs from flowering to seed filling (Hungria et al, 1985;Soratto et al, 2013b), the results showed that regardless of when the NT system was adopted, the application of N at pre-sowing increased the biomass production by 36 to 40% over management systems without pre-sowing N application (Table 4). This finding indicates the importance of fertilization with N during the initial stages of common bean crop grown in a NT system, regardless of its age.…”
Section: Common Bean Dry Matter and Nutritionmentioning
confidence: 99%
“…The amounts of macronutrients required for uptake and exportation by plants for the production of each ton of pod's fresh matter are shown in Table 4. Lower demand of P and higher demand of N, Ca, and S for the common bean than that observed for snap bean has been reported (Soratto et al, 2013;Pegoraro et al, 2014). Faquin and Andrade (2004) highlighted the vegetable crops larger requirement of K in relation to N, a fact observed by authors such as Grangeiro et al (2004) for watermelon, Silva Júnior et al (2006) for melon, Vidigal et al (2007) for pumpkin and Tetsukabuto and Fernandes et al (2011) for potato.…”
Section: Resultsmentioning
confidence: 73%